2012
DOI: 10.1093/infdis/jis488
|View full text |Cite
|
Sign up to set email alerts
|

A Large, Population-Based Study of 2009 Pandemic Influenza A Virus Subtype H1N1 Infection Diagnosis During Pregnancy and Outcomes for Mothers and Neonates

Abstract: In this large, geographically diverse population, A(H1N1)pdm09 infection increased the risk for hospitalization during pregnancy. Late initiation of antiviral treatment was also associated with an increased risk for hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 17 publications
2
61
2
1
Order By: Relevance
“…Five studies [21, 23, 24, 26, 27] gave complete maternal asthma data (Figure 3). Maternal asthma was demonstrated to increase the risk of acquiring influenza A virus infection during pregnancy ( P <0.00001, RR=1.99, 95% CI: 1.67-2.37).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies [21, 23, 24, 26, 27] gave complete maternal asthma data (Figure 3). Maternal asthma was demonstrated to increase the risk of acquiring influenza A virus infection during pregnancy ( P <0.00001, RR=1.99, 95% CI: 1.67-2.37).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies [20, 21, 24, 26-28] in this meta-analysis included data regarding diabetes. According to the time of diagnosis, these outcomes were divided into three groups: diabetes mellitus before pregnancy (DM), gestational diabetes (GDM) and DM/GDM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While this finding is subject to some limitations, it suggests the possibility of pregnancy-related differences in influenza severity related to influenza virus type, as has been suggested by other studies [7,8]. One recent study found pregnant women with pH1N1 to be twice as likely to be hospitalized as pregnant women with seasonal influenza [8]. Severity differences related to specific influenza type are also biologically plausible for pregnant women, especially during later trimesters when decreased maternal lung capacity might increase risk for severe disease from influenza virus types [2], such as pH1N1, that target the lower pulmonary lobe [9].…”
Section: Discussionmentioning
confidence: 51%
“…The PFL findings suggest that during the same influenza season, different influenza viruses might predominate among pregnant women than among other groups (Figure 2). While this finding is subject to some limitations, it suggests the possibility of pregnancy-related differences in influenza severity related to influenza virus type, as has been suggested by other studies [7,8]. One recent study found pregnant women with pH1N1 to be twice as likely to be hospitalized as pregnant women with seasonal influenza [8].…”
Section: Discussionmentioning
confidence: 57%